2019
DOI: 10.1016/j.jsams.2018.09.230
|View full text |Cite
|
Sign up to set email alerts
|

The effects of recovery duration on physiological and perceptual responses of trained runners during four self-paced HIIT sessions

Abstract: Objectives: This study aimed to examine the effects of different recovery durations on self-selected running velocities, physiological responses, and ratings of perceived exertion (RPE) in a commonly used high intensity interval training (HIIT) protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 23 publications
6
28
0
2
Order By: Relevance
“…1 Previous research showed that trained runners reach a steady state of around 90 -95% VȮ 2 max / HRmax across repeated 4 min work intervals, independent of an increased recovery duration between bouts. 6,9,26,27 Both Smilios et al, 27 and Schoenmakers 9 reported changes in the O 2 and HR kinetics when recovery durations increased (more so, mean response time was faster when intervals started from a lower metabolic rate), resulting in similar time spent ≥ 90% and 95% VȮ 2 max and HRmax between the different recovery durations, suggesting a comparable physiological load of the AIT protocol. 9,27 Increasing the recovery duration from 1 to 4 min did not significantly affect…”
Section: The Recovery Duration During Rst and Sitmentioning
confidence: 96%
See 4 more Smart Citations
“…1 Previous research showed that trained runners reach a steady state of around 90 -95% VȮ 2 max / HRmax across repeated 4 min work intervals, independent of an increased recovery duration between bouts. 6,9,26,27 Both Smilios et al, 27 and Schoenmakers 9 reported changes in the O 2 and HR kinetics when recovery durations increased (more so, mean response time was faster when intervals started from a lower metabolic rate), resulting in similar time spent ≥ 90% and 95% VȮ 2 max and HRmax between the different recovery durations, suggesting a comparable physiological load of the AIT protocol. 9,27 Increasing the recovery duration from 1 to 4 min did not significantly affect…”
Section: The Recovery Duration During Rst and Sitmentioning
confidence: 96%
“…Lastly, a number of studies have used self-selected (SS) recovery durations in HIIT protocols, in which athletes started subsequent work intervals when they felt 'adequately recovered to exercise at the required intensity'. [5][6][7][8][9][10] While a considerable amount of variation was evident in SS recovery durations across different HIIT protocols, and SS recovery time is potentially dependent on maturation status 7,10 (see figure 1), the current understanding is that athletes can adequately select recovery durations to achieve the required exercise intensities in subsequent work intervals in both RST and SIT (see figure 1) and AIT (see figure 2).…”
Section: Characteristics Of All Reviewed Studies Are Summarized In Sumentioning
confidence: 99%
See 3 more Smart Citations